Endoscopic biliary drainage in patients with cholangiocarcinoma – self-expanding metal versus polyethylene stents. (4th May 2019) - Voigtländer, Torsten; Schweitzer, Nora; von Hahn, Thomas; Manns, Michael P.; Vogel, Arndt; Kirstein, Martha M.
Abstract: Background: Endoscopic biliary drainage is the standard of care for patients with cholangiocarcinoma (CCA)-induced, obstructive jaundice. Self-expanding metal stents are supposed to be superior to polyethylene stents in terms of reduction of interventions and costs. So far, there are only few real-life data with respect to stent selection and survival in this patient cohort. Methods: In this study, we retrospectively analyzed patients with CCA treated with endoscopic biliary drainage from 2000 to 2015 at Hannover Medical School, Germany. The aim of this study was to analyze whether metal stenting reduces the frequency of interventions and influences survival in a large, real-life cohort. Results: Overall, 422 patients with CCA were included in this study. Indication for endoscopic biliary drainage was most often obstructive jaundice ( n  = 397; 94.1%). Among these patients, 20 patients (5%) were initially treated with a metal stent and 38 (9.6%) received a metal stent in the subsequent course. Median number of interventions per month was 2.4-fold reduced following metal stenting. Patients first treated with a metal stent had a more advanced tumor stage and a significantly shorter median overall survival (mOS) compared to patients who received a metal stent subsequently (7.5 months vs . 15.2 months; p =.019). There was no difference in mOS for metal vs . polyethylene stenting following a propensity score match for the confounders curative resection and chemotherapy (13.2 vs . 13.7 months, p =.555). Conclusions: Our data confirm that metal stenting reduces the frequency of interventions, but does not influence OS. Metal stenting should be considered specifically in younger patients who are suitable for chemotherapy.